Discriminatory pre-hoarding handling and hoarding behaviour towards germinated acorns by Niviventer confucianus. Issue 1 (2nd January 2018) - Zhang, Yifeng; Li, Wei; Sichilima, Alfred M.; Lu, Jiqi; Wang, Zhongquan
Abstract : Germination is an important stage in the seed life cycle, but it decreases seed nutrients and increases secondary compounds, which is disadvantageous to seed hoarders or consumers. Therefore, seed hoarders often use pre-hoarding handling behaviour (PHB) to prevent the further deterioration of germinated seeds. Although PHB is an important component of seed dispersal ecology, few studies have described or estimated the effectiveness of PHB. In this study, we investigated the PHB and hoarding strategies of Niviventer confucianus Milne-Edwards towards germinated and ungerminated acorns ( Quercus variabilis Bl.). We observed that N. confucianus (1) displayed radicle-excision behaviour towards germinated acorns; (2) often removed the pericarps of the germinated acorns more than those of ungerminated acorns before hoarding; and (3) tended to larder-hoard ungerminated acorns but scatter-hoard germinated acorns. Our results indicate that (1) PHB towards germinated seeds exists in this species as well as in members of the family Sciuridae; (2) N. confucianus consumed and hoarded acorns in different condition discriminately, and adopted a flexible strategy when hoarding perishable seeds. These pre-hoarding handling and hoarding behaviours are possibly evolutionary adaptations in rodents to manage and hoard easily germinated acorns and inevitably impacts on seed dispersal, seed fate, seed germination, and sapling recruitment.